PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN MANAJEMEN LABA TERHADAP PENGHINDARAN PAJAK (Studi pada Perusahaan Non-keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Budiharto, Valentinus Arjuna; Fuad, Fuad (Diponegoro Journal of Accounting, 2024)
Companies are required to pay taxes and be responsible to society by disclosing CSR. Agency theory states that companies view corporate expenses as agency costs that must be minimized. Companies use CSR costs as an earnings management strategy. CSR costs are considered a deductible expense to obtain low taxes. This strategy is called earnings management, as a first step to tax avoidance. This study aims to explain and analyze the effect of CSR disclosure and earnings management on tax avoidance.This research method is a quantitative method with a population of non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2019 - 2022. Sampling using purposive sampling technique with 84 sample results from 21 companies in 4 years. Tax avoidance is measured using Effective Tax Rates (ETR) by assessing the tax burden on profit before tax. CSR disclosure is measured by the Global Report Initiative (GRI-G4) based on the identification of items in the sustainability report with the content analysis method. Earnings management is measured using Discretionary Accruals (DA) or Jones Model. The analysis conducted is multiple liner analysis with the Generalized Least Square (GLS) method with E-views version 10 as an analytical tool.The results of this study explain that CSR disclosure has a negative effect on tax avoidance practices. Extensive CSR disclosure means that the company avoids tax avoidance practices. In the second test, earnings management has a positive effect on tax avoidance practices because the main motivation for earnings management is tax avoidance. In the third test, CSR has a negative effect on earnings management because with the company's responsibility to society and the surrounding area in accordance with stakeholder theory, companies tend not to carry out earnings management.